Synthesis, analgesic and anti-inflammatory activities of substituted benzoylthioureas - Tutuk Budiati; Suzana .; Siti Surdijati (Indonesian Journal of Pharmacy, 2010)
Three compounds (i.e.  benzoylthiourea,  4-nitrobenzoylthiourea,  and  4-chlorobenzoylthiourea) have  been  synthesized  from  ammonium  thiocyanate, substituted benzoyl chlorides, and ammonia as starting materials. The structures of  sythesized  compounds  were  confirmed  by  means  of  ultra-violet,  infrared, magnetic resonance, and mass spectroscopy. All compounds were evaluated for their  analgesic  and  anti-inflamatory  activities  by  tail-flick  technique  and carragenan-induced  paw  oedema  test  respectively.  Substitution of p-NO2 and p-Cl  group  to  benzoylthiourea  increased  the  analgesic  and  anti-inflamatory activities.  The  two  compounds,  4-nitrobenzoylthiourea  and  4-chlorobenzoylthiourea,  were  significantly  more  potent  as  analgesic  but  their  antiinflamatory actvity was weaker than Na-diclofenac.Keywords: benzoylthioureas, p-Cl dan p-NO2substituents, analgesic and anti-inflamator activities